Enhancing Artistic Heritage Education through Gamification: A Comparative Study of Engagement and Learning Outcomes in Local Museums - Galindo-Durán, Alejandro (Utan Kayu Publishing, 2025)
This study investigates the impact of gamification on a museum visit compared to a traditional guided tour. A quasi-experimental design with pretest and posttest tests is used to evaluate the effects of each type of visit through statistical analysis of comparison of means with Student's t-test or Wilcoxon test. The research, carried out over several years, involved 68 students of the Master's Degree in Teacher Training, evaluating both the knowledge acquired after the visit and their ability to explain the museum and its cultural and artistic heritage to future students. The results show significant differences between the gamified visits and those carried out with a traditional system. It is evident that gamification not only increases participation and motivation, but also improves knowledge about the exhibition space, suggesting that this methodology promotes a more immersive and participatory learning. These findings may be useful for designing educational experiences in museums that wish to improve their didactic proposal, as well as for teachers interested in conducting excursions that reinforce learning about local heritage.